Impact of soil inorganic nitrogen on bacterial phylogeny in estuarine intertidal zones: a study of nitrogen metabolism - Li, Siqi; Liu, Tianyang; Liu, Cheng; Sun, Donglei; Yan, Qin; Gao, Dengzhou; Zhang, Zongxiao (Frontiers in Microbiology, 2024)
Abstract： Here we investigated the potential impacts of soil inorganic nitrogen (SIN) content on the phylogenetic characteristics and ecological functions of soil bacterial communities in estuarine intertidal zones in China, aiming to comprehend the response mechanism of soil microorganisms to variations in SIN content within estuarine wetlands. Our results show that SIN in estuarine areas has a significant spatiotemporal variation on spatial and seasonal scales, in this study and is significantly associated with the phylogenetic diversity and phylogenetic turnover of soil bacterial communities. In addition, the results of the metagenomic analysis showed that the relative abundance of nitrogen-cycling functional genes in bacterial communities did not differ significantly in sampling sites and seasons, and weakly correlated with SIN content. Further, the results based on structural equation modeling (SEM) analysis showed that SIN directly and significantly regulated the phylogenetic characteristics of bacterial communities, thereby indirectly affecting the potential of bacterial nitrogen metabolism. This study emphasizes the key influence of SIN variations on the phylogenetic dissimilarity in soil bacterial communities. Moreover, although there was a weak direct relationship between the functional characteristics of the bacterial nitrogen metabolism and SIN content, the spatiotemporal variation of bacterial nitrogen metabolic potential may be indirectly regulated by SIN content by influencing the phylogenetic diversity in bacterial communities. Our study unravels the pivotal mechanisms through which SIN content influences bacterial communities, thereby offering novel insights into the microbial intricacies governing nitrogen metabolism within estuaries.